COVID-19: Clinical profile of patients in a hospital in the State of Sergipe (Research, Society and Development, 2021)
Due to the recent outbreak of the coronavirus, millions of people have been affected worldwide. Symptoms such as fever, cough, fatigue and dyspnea are more prevalent in patients with comorbidities. Conduct a reserch of epidemiological, clinic symptons and comorbidities in patients with COVID-19 in serious and mild conditions in a Hospital in the state of Sergipe.  A descriptive study was performed, through a data collection from records of patients infected with COVID-19 at the Regional public Hospital of Itabaiana Dr. Pedro Garcia Moreno, located in Itabaiana, in a period of three months. The total sample was 64 volunteers, being divided into two groups of 32 patients, one group in a mild condition (GC) and another group in a serious condition (GT) The mean age of the present study was 58.3 years, with males (68.5%) and pheoderm ethnicity (62.5%) being more prevalent. The average systolic blood pressure (SBP) was 122 mmHg and the average diastolic blood pressure was 79.8 mmHg. The present symptoms was asthenia (90.63%), dyspnea (84.38%), headache (73.44%), cough (68.8%), fever (65.6%), dysgeusia (54.7%), sore throat (6.26%) and diarrhea (4.7%).  The most prevalent comorbidities were Systematic Arterial Hypertension (SAH) of 42.8% and Diabetes Mellitus (DM) of 15.63%. It is concluded that the most affected ethnicity was pheoderm, the most common symptom in both groups (GT and GC) was asthenia and diarrhea was the least prevalent symptom in both groups. The most prevalent comorbidities were SAH and DM.